User participation in mass house design - Reis, Antônio (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
The lack of user satisfaction with mass housing design has been largely referred to in the literature, among the low to low-middle income groups. Within the objective of reaching a degree of user satisfaction with his/her housing environment, two main schools of thought have emerged: the environment behavior research school of thought and the design participation school of thought. The main reason for the lack of user satisfaction with mass housing design has been attributed by those in the design participation school of thought to the control by architect over design decisions with no user participation at all. This paper assesses, through the use of five indicators, the claims of the design participation school of thought, that successful mass housing might be produced only through the effective participation of future users in decisions concerning the design of housing units and the design of housing scheme, either during the design process or during the occupation of housing units, by means of alterations and appropriations of spaces. The empirical work comprises three state financed mass housing schemes for low-middle income people in the estate of Rio Grande do Sul, Brazil.